Profile of Tuberculosis in Children in Taman District, Sidoarjo Regency, Indonesia - Oktaviani, Ranti Dewanti; Lestari, Pudji; Maranatha, Daniel; Setyoningrum, Retno Asih (Folia Medica Indonesiana, 2022)
Highlight: • Pediatric tuberculosis patients profile using the medical records was determined. • The most pediatric tuberculosis patients under five years have pulmonary tuberculosis. • Pediatric tuberculosis patients received BCG immunization had a contact with adult tuberculosis patients histories. Abstract: The prevalence of tuberculosis (TB) in Indonesia is 391 per 100,000 population with the number of deaths around 110,000 cases in 2016. This study is descriptive research that aims to determine the profile of pediatric TB patients using the medical records at Taman public health center the period 2016-2019 with a total sampling technique. The sample in this study were 31 pediatric patients aged 0-14 years with a history of TB. Pediatric TB patients aged >5 years (58.1%) and who aged â‰¤5 years (41.9%). Pediatric TB patients had pulmonary tuberculosis (83.9%) and those who had extrapulmonary tuberculosis (16.1%). Pediatric TB patients aged â‰¤5 years had good nutritional status (32%) and who had poor nutritional status (27.2%). Meanwhile, pediatric TB patients aged >5 years had poor nutritional status (22.7%) and who had good nutritional status (18.1%). Pediatric TB patients who had a history of contact with adult TB patients (86.7%) and who did not have a history of contact with adult TB patients (13.3%). Pediatric TB patients who had received BCG immunization (86.2%) and who had not received BCG immunization (13.8%). This study concludes that most pediatric TB patients are >5 years old, almost all pediatric TB patients have pulmonary tuberculosis. Pediatric TB patients aged â‰¤5 years are more likely to have good nutrition. Meanwhile, there were more pediatric TB patients aged >5 years who had poor nutritional status. Almost all pediatric TB patients had a history of contact with adult TB patients and had received BCG immunization.